Burying our mistakes: Dealing with prognostic uncertainty after severe brain injury. (2nd March 2020) - Graham, Mackenzie
Abstract: Prognosis after severe brain injury is highly uncertain, and decisions to withhold or withdraw life‐sustaining treatment are often made prematurely. These decisions are often driven by a desire to avoid a situation where the patient becomes 'trapped' in a condition they would find unacceptable. However, this means that a proportion of patients who would have gone on to make a good recovery, are allowed to die. I propose a shift in practice towards the routine provision of aggressive care, even in cases where the probability of survival and acceptable recovery is thought to be low. In conjunction with this shift, I argue in favour of a presumption towards withdrawing life‐sustaining treatment, including artificial nutrition and hydration, when it becomes clear that a patient will not recover to a level that would be acceptable to them. I then respond to three potential objections to this proposal.